Analysis on the future energy demand in Malaysia / Nardia Zubir - Nardia , Zubir (2012)
Malaysia as a rapidly developing country has a very unique energy profile with mixed energy resources such as oil, natural gas, hydroelectric potential and coal. The production of the crude oil and petroleum products in Malaysia is expected to decline from year to year. Natural gas is the major contributor to current trending of electricity generation while coal is expected to be the major contributor for the future pattern of the electricity generation in Malaysia. The industrial sector is expected remain to be the largest consumer of energy in Malaysia; while the electricity consumption from residential and commercial sectors is expected to increase and become the major consumer in the electricity generation. This study is mainly about the prediction of future pattern of energy supply, demand, electricity demand, generated, future GDP growth and environmental impact from electricity generation in Malaysia. Most of the data were obtained and collected from National Energy Balance Malaysia Report, Energy Commission of Malaysia and other government bodies. The future potential of emission production can be analyzed and calculated based on data obtained from the total electricity generation and percentage of each type of fuel which is used to generate the electricity. The projections under historical forecasting modeling method indicated that Malaysia’s energy supply and demand are expected to jump 129% and 105% respectively and total electricity demand and generated are expected to increase 58% and 48% respectively from 2012 to 2030. Meanwhile, Malaysia’s population is expected to increase for about 38% and Malaysia’s GDP is expected to average 4.7% from 2012 to 2030. However, it is expected that Malaysia will be fully developed and the economic is expected to be fully matured in year 2021. The emission production from electricity generation also depends on the percentage of the share in fuel mix energy used to generate the electricity; where large emission is produced when usage of coal is at the highest share. Hence, the predicted total of future potential emission production from 2012 to 2030 are about 7,213,758.78 Mkg of CO2, 76,307.45 Mkg of SO2, 29,619.16 Mkg of NOx and 1,842.38 Mkg of CO.